2013
DOI: 10.1016/j.biopsych.2012.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer Risk Variant CLU and Brain Function During Aging

Abstract: Background We examined the effect of the novel Alzheimer's disease (AD) risk variant rs11136000 single nucleotide polymorphism (SNP) in the clusterin gene (CLU) on longitudinal changes in resting state regional cerebral blood flow (rCBF) during normal aging and investigated its influence on cognitive decline in pre-symptomatic stages of disease progression. Methods Subjects were participants in the Baltimore Longitudinal Study of Aging. A subset of 88 cognitively normal older individuals had longitudinal 15O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 32 publications
5
56
4
Order By: Relevance
“…CLU was associated with cognition in three domains in four studies: general cognition (3MS 16 and a composite score 34 ), episodic memory 35 and verbal memory. 36 However, in the study reported by Mengel-From et al, 34 CLU was not associated with MMSE as in our study and the association with verbal memory was observed only in the subset of patients who subsequently developed LOAD or Mild Cognitive Impairment. 36 This latter result was interpreted as reflecting an association between CLU and pre-symptomatic stage of LOAD but not between CLU and normal ageing.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…CLU was associated with cognition in three domains in four studies: general cognition (3MS 16 and a composite score 34 ), episodic memory 35 and verbal memory. 36 However, in the study reported by Mengel-From et al, 34 CLU was not associated with MMSE as in our study and the association with verbal memory was observed only in the subset of patients who subsequently developed LOAD or Mild Cognitive Impairment. 36 This latter result was interpreted as reflecting an association between CLU and pre-symptomatic stage of LOAD but not between CLU and normal ageing.…”
Section: Discussioncontrasting
confidence: 68%
“…36 However, in the study reported by Mengel-From et al, 34 CLU was not associated with MMSE as in our study and the association with verbal memory was observed only in the subset of patients who subsequently developed LOAD or Mild Cognitive Impairment. 36 This latter result was interpreted as reflecting an association between CLU and pre-symptomatic stage of LOAD but not between CLU and normal ageing. 36 PICALM was associated with general cognition (3MS) in the study reported by Sweet et al, 16 whereas we did not find any association between PICALM and cognitive function.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Another study investigating longitudinal effects of rs11136000 in elderly individuals did not find any difference in memory performance measured by the California Verbal Learning Test in individuals who remained cognitively normal throughout the study. However, that study did find that, for individuals that converted to mild cognitive impairment (MCI) or AD, C allele carriers showed quicker rates of decline than the T allele carriers (Thambisetty et al, 2013). …”
mentioning
confidence: 94%
“…The CLU variant may also affect neural activity during attention [22] and resting-state alpha-rhythm activity in older healthy subjects [23]. Related neuroimaging studies also suggest that the CLU variant may affect white matter microstructure [24] and hippocampal blood flow [25].…”
Section: Introductionmentioning
confidence: 99%